Netflix Inc. : equity valuation - Alves, José Pedro Fernandes Rito (2018)
The aim of this dissertation is estimating the fair value of one unit of Netflix’s common stock, at the end of the year 2018. Two valuation methodologies are utilized, the first being the Discounted Cash-Flow (DCF) approach and the second being the relative valuation methodology, being the multiples used the P/E, EV/EBITDA and EV/Sales. The valuation output is then compared to the equity research report of Morgan Stanley on Netflix. The valuation output is that Netflix is overvalued in the market, being the fair value of one unit of common stock estimated to be $239,35 at the end of 2018, while the stock is trading at $328,53 on the 15th of May 2018. Hence, the recommendation produced in this dissertation is a sell recommendation. This recommendation is only a function of the DCF approach, since the relative valuation outputs were not consistent across the different multiples used nor with the value computed through the DCF approach. Morgan Stanley estimates the value of one unit of common stock at the end of 2018 to be $275, which is a higher valuation than the one estimated in this dissertation and also yields an opposite recommendation, as Netflix’s stock was trading at $227,58 at the time of valuation. This difference is mainly explained by different assumptions regarding the evolution of Netflix’s FCFFs, as the WACC in both valuations differs only 12 basis points and the perpetual growth rate differs only 17 basis points.